Changes in postnatal transfers and place of delivery following introduction of managed neonatal networks in england. (4th April 2011) - Gale, C; Nagarajan, S; Santhakumaran, S; Statnikov, Y; Modi, N
Abstract : Background: Following a Department of Health review in 2003, specialist neonatal services in England were re-organised into managed clinical networks with the aim of delivering high quality co-ordinated care.1 Maternity services were not included in this re-organisation. Effective network performance should result in reduced acute, and increased in-utero and back transfers among extremely preterm babies. Aims: To test the hypothesis that since establishment of managed networks there has been an increase in the proportion of preterm babies (1) Delivered at units with the greatest intensive care experience, (2) Transferred between age 24 h and 28 days and (3) A reduction in the proportion transferred at age <24 h. Design: Caldicott Guardian approval has been obtained to receive routinely collected data from neonatal units for service evaluation. We compared postnatal transfers in infants born at 27 0 –28 6 weeks days gestational age before (epoch one 1 September 1998–31 August 2000) and after re-organisation (epoch two 1 January 2009–31 December 2009). Information from epoch one was obtained from the Confidential Enquiry into Stillbirths and Deaths in Infancy report on preterm infants2 and for epoch two from the 121 neonatal units contributing routinely collected data for that period, and differences tested for significance (χ 2 test and logistic regression). Results: There were no significant between epoch differences in gender, delivery mode or multiple births. In epoch two, a higher proportion of babies were born in units with greater neonatal intensive care experience (p<0.001); the proportion having an acute transfer ≤24 h increased from 6.8 to 12.7% (p<0.001) and survival improved (p<0.001) (table 1 ). Conclusions: Since reorganisation, a greater proportion of extremely preterm babies are born in the most experienced neonatal units, and a greater proportion undergo both acute and later postnatal transfer. The increase in delivery at experienced units would be expected to improve outcomes. The increase in acute postnatal transfers may suggest that neonatal and maternity services are not functioning effectively in facilitating in-utero transfers. We suggest that focus should be placed on organisation of perinatal networks, and the commissioning disparity between neonatal and maternity services should be rectified. Preterm babies are highly likely to undergo postnatal transfer; this should be explained to parents.